Correlation of Ankle Brachial Index (ABI) To The Risk of Diabetic Wound Ondiabetes Mellitus Type 2 - Yanti, S; ., Murgiyati (KnE Life Sciences, 2019)
Diabetes mellitus is a chronic disease caused by inherited and or acquired deficiency inproduction of insulin by the pancreas, or by the ineffectiveness of the insulin produced. Such a deficiency result in increased concetrations of glucosa in the blood, which in turn damage blood vessel. Peripheral arterial disease (PAD) is a complication of diabetes that happens when blood vessels in the legs become blocked or narrowed due to fat deposits. Diabetic patient with PAD have a high risk to get diabetic wound caused high concetrations of blood. Simple test used to document PAD is measure of the ankle brachial index (ABI). ABI compares the systolic blood pressures of the ankle or legs with brachial or arms to give a ratio that can suggest various severity of PAD. This study aimed to determine the relationship between the ABI and diabetes type 2 patient’s wound risk of type 2 in Santa Maria Hospital Pekanbaru. These study was quantitative research with cross sectional approach with 55 respondents. The study was conducted in April 15 to May 20 2018. The study measured the ABI and anamnese signs and symptoms of PAD. The results of this study showed that there was a relationship between the ABI and wound risk in diabetic type 2 patient in Santa Maria Hospital Pekanbaru (p= 0,000). This study recommended healthcare service do the ABI measurement for diabetes patients to early detection PAD and prevent the diabetic wound. Keywords: ABI, diabetic type 2, wound risk